Nursing Profiles: Rob Calnan, Michael J. Villeneuve, David Gregory (Nursing Leadership, 2004)
Rob Calnan, RN, BScn, MEd Rob Calnan is President of the Canadian Nurses Association (CNA). Mr. Calnan is the nurse manager for burns, plastics, complex wounds, eyes, ears, nose and throat, general surgery, abdominal/thoracic surgery and urology at Royal Jubilee Hospital in Victoria, British Columbia. He received the Queen's Golden Jubilee Medal in 2004 for his contribution to healthcare and was one of four Canadian nurses on an International Council of Nurses delegation to the World Health Assembly. He is an outspoken nursing advocate who writes and speaks about the value of nursing and the future of healthcare in Canada.